Pembekalan Edukasi Pengetahuan Penyakit Degeneratif dengan Penanaman-Pemanfaatan tanaman Toga Serta Perilaku Hidup Bersih dan Sehat (PHBS) Kepada Masyarakat Cawang RT 009 dan RT 011 - Waluyo, Dyah Ayuwati; Krismayadi, Krismayadi; Purnomo, Frida Octavia; Hanan, Raihan Arung; Pramesti, Anggi Shiva; Nusantarawati, Eka; Mulyani, Hanny Dwicahya; Tsabitah, Nadiah; Adiningsih, Septia Nur Wahyu (Jurnal Mandala Pengabdian Masyarakat, 2024)
One of the problems that exists in the people of Kampung Cawang RT 09 & 11 RW 13, Kramat Jati Village, East Jakarta City is a lack of awareness, but quite a few people in Kampung Cawang have basic knowledge regarding degenerative diseases, what are the examples of the disease, the symptoms of each generative disease and how possible therapies can be applied both medically and non-medically, therefore counseling related to degenerative diseases is the main program that has been implemented during the KKN process. Lack of awareness of the potential around them which they might be able to use as additional resources to be useful for Cawang village community education. One of the programs implemented in Cawang village is apart from counseling about degenerative diseases, there are also other programs including counseling about drug classification, how to store drugs, how to wash hands properly and several other additional programs that support the creation of good relationships between students (participants). KKN) with the people of Cawang Village. The objectives of holding this program are: 1) To create public awareness of the importance of science; 2) To create basic knowledge regarding degenerative diseases; 3) To encourage and motivate people to know the importance of science and maintaining health and to be able to cultivate toga independently. The result of this outreach program is that the community is enthusiastic in participating in this activity. Apart from that, this outreach program can also help people who have difficulty understanding the basics of degenerative diseases and maintaining health.